A Case of Extensive Pityriasis Alba - Lee, Deborah (Ann Dermatol, 2008)
Pityriasis alba (PA) is a common benign disease, characterized by hypopigmented macules or patches on the face, usually seen in children. However, two uncommon variants exist, a pigmenting type and an extensive type. Extensive PA is rare. The lesions tend to be less scaly, more persistent, more generalized, more symmetrical, and more frequently seen over the trunk and less so over the face. We report a child who had extensive PA lesions.